Associated efficiency of Saccharomyces cerevisiae and vitamin E in ameliorating adverse effects of ochratoxin A on biochemical profile and immune response in broiler chickens - SINGH, SATYENDRA; SINGH, RAM; MANDAL, A B (The Indian Journal of Animal Sciences, 2019)
The associated efficacy of Saccharomyces cerevisiae and vitamin E, in ameliorating ochratoxicosis was investigated in broiler chickens. Day-old broiler chicks (320) were divided into 8 treatment groups, viz. T1 (control; basal diet); T2 (T1 + 150 ppb OTA); T3 (T2 + 0.05% SC + 100 mg vitamin E-VE); T4 (T2 + 0.075% SC + 100 mg VE); T5 (T2 + 0.1% SC + 100 mg VE); T6 (T2 + 0.05% SC + 200 mg VE); T7 (T2 + 0.075% SC + 200 mg VE) and T8 (T2 + 0.1% SC + 200 mg VE/kg diet). Each diet was fed to 5 replicated groups of 8 birds from 0–42 days of age. The total serum protein, cholesterol and haemoglobin content of control group (T1) was higher than that of ochratoxin fed group (T2). The serum protein, cholesterol and haemoglobin value in groups T5, T7 and T8 was higher than T2 but statistically similar to that of control. The serum uric acid, creatinine, ALP, SGOT, SGPT and H/L ratio value in T1 was lower than that of T2. The uric acid, creatinine, ALP, SGOT, SGPT and H/L ratio value in T5, T7 and T8 was lower than T2 and statistically similar to that of control. The CMI and HA titre value of T1 was higher than that of T2. The CMI and HA titre value in T5, T7 and T8 was higher than that of T2 but statistically similar to that of control. It can be concluded that ochratoxin contamination at the rate of 150 ppb in the feed resulted in decreased total serum protein, cholesterol and haemoglobin content and increased serum uric acid, creatinine, ALP, SGOT, SGPT and H/L ratio value. Inclusion of Saccharomyces cerevisiae at 0.1% level along with 100 mg vitamin E or Saccharomyces cerevisiae at 0.075% level along with 200 mg vitamin E/kg diet to the ochratoxin (150 ppb) contaminated feed ameliorated the adverse effects of ochratoxicosis on biochemical profile and immune response in broiler chickens.